Green tribology : biomimetics, energy conservation and sustainability - Bhushan, Bharat; Nosonovsky, Michael (Green Energy and Technology, 2012)
Tribology is the study of friction, wear and lubrication. Recently, the concept of "green tribology" as "the science and technology of the tribological aspects of ecological balance and of environmental and biological impacts" was introduced. The field of green tribology includes tribological technology that mimics living nature (biomimetic surfaces) and thus is expected to be environmentally friendly, the control of friction and wear that is of importance for energy conservation and conversion, environmental aspects of lubrication and surface modification techniques, and tribological aspects of green applications such as wind-power turbines or solar panels. This book is the first comprehensive volume on green tribology. The chapters are prepared by leading experts in their fields and cover such topics as biomimetics, environmentally friendly lubrication, tribology of wind turbines and renewable sources of energy, and ecological impact of new technologies of surface treatment.